Respuesta :

Answer:

(x,y) (-3,4)

Step-by-step explanation:

Answer: [tex]x = -3[/tex] and [tex]y = 4[/tex]

Step-by-step explanation:

[tex]2x+5y = 14[/tex] ....................... equation 1

[tex]6x+7y = 10[/tex] ....................... equation 2

Using elimination method

multiply equation 1 by (3) and equation 2 by (1)

Then we have:

[tex]6x + 15y = 42[/tex]    .................. equation 3

[tex]6x + 7y = 10[/tex] ................... equation 4

subtract equation 4 from equation 3 , we have

[tex]8y = 32[/tex]

divide through by 8

[tex]y = 4[/tex]

substitute [tex]y = 4[/tex] into equation 1 to get the value of x

that is :

[tex]2x + 5(4) = 14[/tex]

[tex]2x + 20 = 14[/tex]

[tex]2x = 14 - 20[/tex]

[tex]2x = -6[/tex]

[tex]x = -3[/tex]

Therefore:

[tex]x = -3[/tex] and [tex]y = 4[/tex]